Quantitative detection of shallow subsurface cracks in pipeline with time-of-flight diffraction technique. (March 2021) - Jin, S.J.; Sun, X.; Luo, Z.B.; Ma, T.T.; Lin, L.
Abstract: When the ultrasonic time-of-flight diffraction (TOFD) technique is applied to the inspection of pipeline, the propagation direction of the direct longitudinal wave is not parallel to the pipe surface, leading to the increment of the depth of dead zone and the measurement errors of shallow subsurface cracks. In this paper, the differences between the dead zones in flat plate and pipeline are compared theoretically. Subsequently, the method based on the mode-converted waves in TOFD B-scan image, which has been used for reducing the dead zone in flat plate, is developed to restrict the dead zone in pipeline and to realize the accurate measurement of shallow subsurface cracks. The simulated and experimental results indicated that the depth of dead zone in the carbon steel pipeline with a radius of 148 mm was reduced from 6.3 mm to 3.0 mm and that the measurement errors of crack length and angle were no more than 0.27 mm and 1.57°, respectively. The depth of the dead zone in pipeline and the measurement errors before modification both increase with the reduction of the ratio of pipe radius to probe center spacing (PCS). The modified method has universality for the detection of the shallow subsurface cracks in pipeline with ultrasonic TOFD technique.